Safety evaluation of directly observed treatment short course (DOTS) regimen in a tertiary care hospital, Pune - Dalal, Nishant P.; Karandikar, Yogita S.; Pandit, Vijaya A. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Directly observed treatment short course (DOTS) is a cornerstone of Revised National Tuberculosis Control Program of India. Adverse drug reactions (ADRs) induced by this therapy is common and it causes significant morbidity and mortality. Hence, the present study was undertaken to determine the incidence and pattern of ADRs and to assess causality and severity. Methods: We conducted prospective, observational study at DOTS center of tertiary care hospital, Pune. 150 pulmonary tuberculosis patients undergoing DOTS therapy were enrolled. They were monitored weekly in an intensive phase and monthly in the continuation phase. The suspected ADRs were recorded and assessed for causality and severity by standard algorithms. Results: Incidence of ADRs due to DOTS was 19.33% & total 35 ADRs had occurred in our study. Gastrointestinal intolerance, arthralgia & itching with or without rashes were most common ADRs (incidence rates: 12.67%, 2.67% and 2.67%, respectively). On evaluation of causality by Naranjo algorithm, majority of ADRs 91.43% were “possible.” As per WHO- Uppsala Monitoring Center scale, majority of ADRs 91.43% were “possible.” As per Modified Hartwig and Siegel scale, majority of ADRs were “moderate” (48.57%) but 8.57% were “severe.” Female gender was found to be a significant risk factor for developing ADRs (odds ratio: 3.08, 95% confidence interval: 1.33-7.12. 3.33%). ADRs & hepatotoxicity was major reason for defaulting from DOTS (60%). Conclusion: ADRs induced by DOTS are common and there is need of incorporating pharmacovigilance system for this vital public health program. Counseling of patients for timely prevention, detection, and management of ADRs will help in minimizing the further occurrence of ADRs.